Study on the Biological Effects of Oligochitosan Fractions, Prepared by Synergistic Degradation Method, on Capsicum - Pham Dinh Dung; Le Thanh Hung; Tran Le Truc Ha; Le Quang Luan; Bui Van Le; Nguyen Tien Thang (International Journal of Polymer Science)
Chitosan with an initial molecular weight (Mw) of approximately 193 kDa was degraded into about 11.4 and 14.8 kDa by γ-ray irradiation of the solution containing 5% chitosan in 0.2 M acetic acid at 75 kGy and the solution of 5% chitosan in 0.2 M acetic acid supplemented with 1% H2O2 at 10 kGy, respectively. The synergistic degraded chitosan sample with Mw ~14.8 kDa was separated into 5 fractions by using ultrafiltration membranes. The analysis results from UV, FTIR, and NMR spectra indicated that the combined treatment of low irradiation dose and low H2O2 concentration did not cause any change in the molecular structure of degraded chitosan fractions. Separated chitosan fractions with Mw > 1 kDa inhibited the growth of Colletotrichum capsici in vitro. While all separated chitosan fractions remarkably enhanced fresh biomass (11–56%) and chlorophyll content (20–92%) of capsicum seedlings. In the field test, the treatment with oligochitosan fractions with Mw in a range of 1–3 kDa (F2) to 3–10 kDa (F3) gained 9.0–11.4% of the fruit yield and reduced 64.8–67.2% of the rate of anthracnose disease outbreak fruits caused by C. capsici. Thus, the F2 and F3 fractions in degraded chitosan product are the key fractions for the enhancement of both the growth promotion effect and defense respond activity against the infection of pathogenic Colletotrichum fungi causing anthracnose disease in capsicum.